RAM (reliability, availability and maintainability) of threshing machine in agriculture - Sharma, Anchal; Ailawalia, Praveen; Shakuntala (Agriculture and Natural Resources, 2022)
The performance of agricultural machinery is affected by their reliability, availability, the environment where a machine is operated, the process, the efficiency of maintenance and most of all, the technical expertise of the user. The impacts of increased machinery failure rates have become more important as the size and complexity of farm equipment has increased, which makes reliability, availability and maintainability analysis more important. Three states of the system were considered in this paper: good state, reduced state and failed state. The formulation of the problem involved using a supplementary variable technique and the solution was obtained by applying Lagrange’s method. The results indicated there was scope to increase the efficiency of any system by reducing its failure rate, specifically, the mean time between failures, the mean time to failure and the mean down time.